Keterampilan Transversal dalam Pendidikan: Tinjauan Sistematis Berpanduan PRISMA tentang Tren, Tema, dan Kesenjangan Riset - Haryanto Haryanto; Warju; Soeryanto; Achmad Imam Agung; Puput Wanarti Rusimamto (Jurnal Educatio FKIP UNMA, 2026)
Transversal skills are increasingly regarded as core competencies in education because they support learners’ critical thinking, collaboration, communication, creativity, problem-solving, and adaptability. However, the dispersion of research on transversal skills across various terms, contexts, and approaches necessitates a more focused synthesis. This study aims to analyse publication trends, major themes, educational contexts, research approaches, and gaps in studies on transversal skills. The study employed a systematic literature review, with reporting guided by PRISMA 2020. The search was conducted in Scopus and was limited to English-language, open-access journal articles published between 2021 and 2026. Out of the 117 records found, 16 articles met the requirements for inclusion. The review findings show that there were more publications between 2021 and 2025. The most common topics were conceptual refinement, perception-based measurement, active and collaborative pedagogy, open schooling, and the use of technology, STEM, the arts, and AI. The synthesis also shows that transversal skills are more frequently developed through authentic, collaborative, and project-based learning, although the field is still characterised by the dominance of cross-sectional designs, self-report measures, and limited use of authentic assessment. This review emphasises the need to strengthen operational definitions, expand the vocational high school/TVET context, and develop longitudinal evidence to enhance the relevance and sustainability of transversal skills development in education.